A Usability Evaluation of a Touchscreen Workstation on Wheels in a Simulated Emergency Department Workflow. - Razzaq, Saad; Idrissi, Omar; Rose, Jake; Marquez, Santiago; Correa, Jose; Robert, Antony (McGill Journal of Medicine, 2025)
Background: Touchscreens have become ubiquitous in our daily lives, offering a comfortable and natural human-technology interactive experience. There exists a gap in the literature regarding the usability and efficiency of a touchscreen workstation on wheels (WOW) within an emergency department (ED) workflow, specifically with electronic medical record (EMR) systems designed for keyboard and mouse. Methods: This was a randomized, controlled, 2-intervention-2-period crossover study comparing a touchscreen to a non-touchscreenWOW. Participants were asked to complete a series of seven tasks that are typically done in the ED followed by the completion of a post-study questionnaire. Results: A total of 24 people (12 attendings, 12 resident physicians) participated in the study. Results from the linear mixed model regression analyses showed no evidence to reject the hypothesis that the average time to complete each task and the average total time to complete all tasks combined were similar (p>0.05) between the touchscreen and nontouchscreen WOW. Results from the post-study questionnaire using a 7-point Likert scale (Figure 1) demonstrated that the majority (>50%) of participants agreed to most questions favoring intention to use (BU), ease of use (PEOU), perceived usefulness (PU), and attitude towards utilization (AU) of the touchscreenWOW. Conclusion: This study builds on previous work on touchscreen devices by specifically evaluating the usability and efficiency of touchscreen WOWs in a controlled, simulation-based setting, differentiating from prior studies on tablets at the bedside. Future studies, should evaluate the impact of touchscreen-friendly EMR designs on clinical workflows in the ED.